2020
DOI: 10.3390/ph13070149
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Clinical Doses of Tramadol and Tapentadol Causes Hepato- and Nephrotoxic Effects in Wistar Rats

Abstract: Tramadol and tapentadol are fully synthetic and extensively used analgesic opioids, presenting enhanced therapeutic and safety profiles as compared with their peers. However, reports of adverse reactions, intoxications and fatalities have been increasing. Information regarding the molecular, biochemical, and histological alterations underlying their toxicological potential is missing, particularly for tapentadol, owing to its more recent market authorization. Considering the paramount importance of liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 229 publications
(431 reference statements)
2
19
0
2
Order By: Relevance
“…Collectively, our results show that lung, heart, and brain cortex toxicological damage occurs at the biochemical, metabolic, and histological levels upon exposure to clinical doses of tramadol and tapentadol (Figure 9). As seen in our study addressing hepatorenal toxicity following consecutive opioid administration [57], lower therapeutic doses are able to induce injury if administered repeatedly. Damage accumulates along lengthier exposure periods than those we have previously assayed [55,56], but shorter than those employed in most peer studies.…”
Section: Repeated Exposure To Tramadol and Tapentadol Leads To Histopmentioning
confidence: 65%
See 4 more Smart Citations
“…Collectively, our results show that lung, heart, and brain cortex toxicological damage occurs at the biochemical, metabolic, and histological levels upon exposure to clinical doses of tramadol and tapentadol (Figure 9). As seen in our study addressing hepatorenal toxicity following consecutive opioid administration [57], lower therapeutic doses are able to induce injury if administered repeatedly. Damage accumulates along lengthier exposure periods than those we have previously assayed [55,56], but shorter than those employed in most peer studies.…”
Section: Repeated Exposure To Tramadol and Tapentadol Leads To Histopmentioning
confidence: 65%
“…Decreased brain glutathione, glutathione peroxidase, and superoxide dismutase (SOD) activities, as well as increased brain malondialdehyde (MDA), nitric oxide (NO), inducible nitric oxide synthase (iNOS), and 8-hidroxydeoxyguanosine levels, have been described in mice and rat models repeatedly administered with 20 to 168 mg/kg tramadol, through different routes [ 60 , 62 , 67 , 68 , 69 , 70 , 71 ]. Furthermore, under the conditions assayed in the present study, we have previously shown increased TBARS—a surrogate of lipid peroxidation (LPO)—and protein carbonyl groups—indicative of protein oxidation—in liver and kidney homogenates from Wistar rats exposed to both tramadol and tapentadol [ 57 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations